I love my new toy! - Willems, Mo. (New York : Hyperion Books for Children, 2008)
When Elephant accidentally breaks Piggie$1 (Bs new toy, they both experience intense feelings before coming to realize how important their friendship is.s
Keywords: Friendship -- Fiction; Emotions -- Fiction; Elephants -- Fiction; Pigs -- Fiction